2015
DOI: 10.1002/bem.21925
|View full text |Cite
|
Sign up to set email alerts
|

Occupational EMF exposure from radar at X and Ku frequency band and plasma catecholamine levels

Abstract: Workers in certain occupations such as the military may be exposed to technical radiofrequency radiation exposure above current limits, which may pose a health risk. The present investigation intended to find the effect of chronic electromagnetic field (EMF) exposure from radar on plasma catecholamines in the military workforce. In the study, 166 male personnel selected randomly were categorized into three groups: control (n = 68), exposure group-I (X-band, 8-12 GHz, n = 40), and exposure group-II (Ku-band, 12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…The frequency of the radar systems ranges from 1 GHz to 300 GHz [ 7 , 41 , 42 ] and this variability of the frequencies depends on the application (i.e., control radars, weather radar, etc.). Indeed, the radar spectrum can be divided into 11 parts, where each part identifies a band: L-, S-, C-, X-, Ku-, K-, Ka-, V-, W-band [ 13 ].…”
Section: Resultsmentioning
confidence: 99%
“…The frequency of the radar systems ranges from 1 GHz to 300 GHz [ 7 , 41 , 42 ] and this variability of the frequencies depends on the application (i.e., control radars, weather radar, etc.). Indeed, the radar spectrum can be divided into 11 parts, where each part identifies a band: L-, S-, C-, X-, Ku-, K-, Ka-, V-, W-band [ 13 ].…”
Section: Resultsmentioning
confidence: 99%
“…Symbols in grey represent data published before 2012 and symbols in black data published in or after 2012. Literature references used: 27,53,57,69,71,76,80,[93][94][95][96][97][98][99][100][101][102][103][104][105]…”
Section: Discussion 13mentioning
confidence: 99%
“…Two studies found that increased melanoma risk was also branch-dependent, with the highest rates among the United States Air Force. Several reviewed studies implicated increased sun exposure during military service and lack of sufficient sun protection as the causes of higher rates of skin cancer among US military and veteran populations as compared with non-military population in the United States [ 111 ] ( Table 10 ).…”
Section: Sunlight Exposurementioning
confidence: 99%
“…Indeed, after an initial period characterized by high stress levels and consequent enhanced production of adrenaline, biological systems tried to find a new homeostasis with reduced adrenaline levels to restore normal functioning. Regarding group I, the authors explained that radar frequency band and years of exposure were not sufficient to induce a stress response [ 111 ]. Sobiech et al evaluated electromagnetic fields-exposure of Polish military personnel by measuring 204 devices divided into four groups: airport radars and radio navigation system, aircraft and helicopters, surveillance and height finder radars, and communication devices.…”
Section: Electromagnetic Fieldsmentioning
confidence: 99%